Directed evolution and modular integration of a high-affinity ICOS-L variant for potent T cell–mediated tumor elimination - Ji Yeon Ha; Tae Wook Song; Petrina Jebamani; Sun-Gu Lee; Sang Taek Jung (Journal of Biological Engineering)
Abstract Background Advancing cancer immunotherapy requires engineering synthetic immunomodulators that integrate precise receptor targeting, tunable activity, and compatibility with modular biologic formats. The Inducible T-cell Co-Stimulator (ICOS) is a clinically validated co-stimulatory receptor whose engagement enhances T-cell function. However, the development of ICOS-targeting biologics has been hindered by limited receptor affinity and format-dependent agonist activity. To address this, we applied a protein engineering framework to optimize the ICOS ligand (ICOS-L) as a high-affinity, modular component for precision immune modulation. Results Using yeast surface display–based directed evolution, we identified an ICOS-L variant (Y8) containing two synergistic mutations (Q51P and N57H) that improved human ICOS (hICOS) binding affinity by ~ 100-fold relative to wild-type. Structural modeling revealed that Q51P enhances backbone rigidity via a proline-induced conformational constraint, while N57H introduces a salt bridge with Asp86 in hICOS. These mutations reconfigure the receptor-binding interface to support high-affinity engagement. Functionally, Y8 induced potent T-cell proliferation and IFN-γ secretion. When genetically fused to pembrolizumab, Y8 further enhanced T-cell activation and tumor cell lysis, demonstrating synthetic synergy between PD-1 blockade and ICOS agonism. Among fusion formats, light-chain conjugation (pembrolizumab-L-Y8) exhibited superior functional output, highlighting the importance of geometric configuration in optimizing fusion-based agonism. Conclusion This study establishes Y8 as a high-affinity ICOS-L variant with robust co-stimulatory function, capable of potentiating anti–PD-1 immunotherapy through modular fusion design. The integration of Y8 into therapeutic antibody scaffolds provides a versatile engineering framework for the development of next-generation immunomodulatory biologics, offering opportunities to overcome resistance and enhance clinical efficacy in cancer immunotherapy.